Book Review: South Korea’s Engagement with Africa: A History of the Relationship in Multiple Aspects - Burghart Sabine (Routledge, 2022)
edited by Yongkyu Chang, Singapore, Palgrave Macmillan, 2020, xviii + 196 pp., eBook: €74,89 (hardcover: €98,99), ISBN: 978-981-32-9013-6, https://doi.org/10.1007/978-981-32-9013-6_1